Early Postoperative 18F-FDG PET/CT in High-Risk Stage III Colorectal Cancer. (April 2015) - Wasserberg, Nir; Purim, Ofer; Bard, Vyacheslav; Kundel, Yulia; Gordon, Noa; Groshar, David; Goldberg, Natalia; Kashtan, Hanoch; Sulkes, Aaron; Brenner, Baruch
Abstract : Purpose: PET/CT may contribute to staging modification in different phases of colorectal cancer (CRC) management. However, it is not routinely indicated for stage III CRC. This study sought to determine the role of early postoperative PET/CT in patients with high-risk stage III CRC. Patients and Methods: The tumor registry of a tertiary medical center was searched (2004–2011) for all patients with stage III CRC who underwent early postoperative PET/CT because of the presence of high-risk factors for systemic disease. Demographic and clinicopathological characteristics were compared between patients found/not found to have metastatic disease. Results: The cohort included 91 patients with a median age of 67 years (range, 29–90 years). Pathological FDG uptake was observed in 38 (41%). Of these, 14 (15% of the whole cohort) were upstaged with alteration of their treatment protocol, 10 (11%) had local postoperative changes, and 14 (15%) had false-positive findings. The sensitivity and specificity of PET/CT for detecting metastatic disease were 100% and 69%, respectively. Elevated postoperative carcinoembryonic antigen and CA-19.9 levels correlated with a positive PET/CT ( P = 0.05 and P = 0.03, respectively). The median follow-up time was 34 months (range, 4–85 months). The estimated 5-year survival rate was significantly higher in patients with a negative than a positive scan (70% vs 42%, P < 0.0006). Conclusions: Findings on early postoperative PET/CT may influence staging and treatment in 15% of selected patients with high-risk stage III CRC. Postoperative levels of carcinoembryonic antigen and CA-19.9 may serve as indications for PET/CT scanning in this setting. Prospective validation is warranted.